Exploring potential cytokine profiles as diagnostic biomarkers for brucellosis in Mediterranean Buffaloes - Franzoni, Giulia; Signorelli, Federica; Donniacuo, Anna; Schiavo, Lorena; Napoletano, Michele; De Matteis, Giovanna; Grandoni, Francesco; Zinellu, Susanna; Bove, Vincenzo; Dei Giudici, Silvia; De Carlo, Esterina; Galiero, Giorgio; et al. (Frontiers in Veterinary Science, 2025)
Brucellosis is a zoonotic disease, with an important economic impact on the livestock industry and public health worldwide. Both Brucella abortus and Brucella melitensis can infect Mediterranean Buffalo (Bubalus bubalis), leading to infertility and abortion. In ruminants, the standard diagnostic approach involves two serological tests, the Rose Bengal Test and the Complement Fixation Test, applied in parallel, though their specificity requires improvement. Cytokines play a crucial role in coordinating immune responses through complex networks and can serve as biomarkers for various diseases. This study explored the potential use of cytokines as immunological biomarkers for Brucella infection in Mediterranean Buffalo. For this purpose, we included 18 healthy and 20 Brucella-infected buffaloes in our analysis. Heparinized blood samples were stimulated with the Brucella antigen, with PBS as nil control and PWM as lymphocyte viability control. After 16–24 h, plasma levels of IL-1α, IL-1β, IL-4, IL-6, IL-10, IL-17, IL-36Ra, MIP-1α, MIP-1β, MCP-1, CXCL8, IP-10, IFN-γ, TNF, and VEGF-A were measured using multiplex ELISA. Our results showed that infected animals released significantly higher levels of IFN-γ, IP-10, MCP-1 in response to Brucella antigen compared to healthy controls. Conversely, healthy animals released instead higher levels of IL-1α, IL-1β, IL-6 and IL-10 following antigen stimulation compared to infected animals. Finally, sequential canonical discriminant analyses were performed to generate predictive cytokine profiles for each group. The findings indicated that a combination of five cytokines (IFN-γ, IP-10, IL-1α, IL-1β, IL-6) can effectively distinguished infected from healthy buffaloes. Overall, this study suggests that incorporating these key immune cytokines could improve the diagnostic accuracy of brucellosis in Mediterranean Buffalo.